HUBUNGAN ANTARA KEBIASAAN OLAHRAGA DENGAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS TIPE 2 (Studi di Puskesmas Rowosari Kota Semarang Tahun 2018) - Fany Fanana Mahdia; Henry Setyawan Susanto; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Controlling bloods glucose levels is the most important thing for patients T2DM to reduce the risk of complications. It was found that uncontrolled blood glucose levels of T2DM patients was greater than controlled one. In addition, it was found that T2DM patients didn’t exercise. Even though, the recommendations for management of T2DM have been given. The aim of the study was to determine the relationship between exercise habits with blood glucose levels. This study used a cross-sectional with a sampling approach for case-control studies. The population was all of T2DM sufferer in Rowosari Health Center who examined blood glucose levels. The 80 research samples consist of 40 groups of controlled and 40 groups of uncontrolled. The sample was choosen based on consecutive sampling, that all subjects who came in sequence and met the criteria were entered until the amount was fulfilled. The collecting data was conducted through interviews using a questionnaire. Data was analyzed using pearson and rank-spearman test. Results refers that there was a relation of exercise frequency with blood glucose levels (p=0,001;r=-0,384), exercise type with blood glucose levels (p=0,002; r=-0,335), exercise duration with blood sugar levels (p=0,015 r=-0,271; r=-0,193). But, isn’t related of exercise intensity with blood glucose levels (p=0,087), time with blood glucose levels (p=0,074; r=-0,201). The conclusion is, there is a relationship between frequency, types, and duration of exercise. There is no relationship between intensity and time of exercise. It is expected that patients with T2DM are able to perform sports activities well, so that blood glucose levels remain controlled.